Environmental benefits of coatings based on nano-tungsten-carbide cobalt ceramics. (1st April 2017) - Wigger, Henning; Steinfeldt, Michael; Bianchin, Alvise
Abstract: Engineered nanomaterials (ENMs) offer improved or novel technical properties and, consequently, are increasingly being used in various applications. Furthermore, ENMs may contribute to a higher eco-efficiency compared to conventional technologies due to decreased materials and energy requirements. Thus far, only a few studies into the environmental performance of ENMs have been conducted and these have mainly focused on the production stage and have not considered a full life cycle thinking approach. Nano-WC-Co coatings are featured to have an improved wear resistance and require less material compared to conventional hard chromium coatings for the same performance in the application. Here, we perform a life cycle assessment to compare the environmental performance of two alternative ceramic coatings for conveyer rolls: novel tungsten-carbide cobalt nanoparticles (nano-WC-Co) and conventional hard chromium. The results of the cradle-to-grave life cycle assessment of nano-WC-Co application showed an overall reduced environmental impact in the main impact categories compared to hard chromium coatings. The most considerable reduction was observed in the categories metal depletion (−98%), water depletion (−91%), agricultural land occupation (−83%). Likewise, the categories human toxicity (−73%) and fresh water eutrophication (−79%) showed a reduced environmental impact. The results were evaluated by a sensitivity analysis and two particularly influential parameters were identified: the efficiency of thermal spraying process, and the extended product lifespan. Overall, it has been shown that nano-WC-Co coatings contribute to a higher eco-efficiency in every sensitivity variation and can offer more sustainable solutions compared to the conventional technology. Highlights: The life cycle of nano-tungsten-carbide cobalt was assessed for the first time. Nano-tungsten-carbide cobalt and conventional chromium coatings were compared. Environmental impacts were reduced in the most categories (up to 98%). Service life and use of secondary materials are important influencing parameters.